Analysis of the B2M Expression in Colon Adenocarcinoma and Its Correlation with Patient Prognosis. (9th August 2022) - Lin, Hailian; Wang, Kelang; Zou, Kebing; Wang, Yuanyuan; Que, Gen xiang; Yang, Xuefeng; Liao, Mengdan
Abstract : Colon adenocarcinoma (COAD) is one of the most common malignant tumors in clinics. It is often found at an advanced stage, with high incidence and poor prognosis; early diagnosis is difficult and treatment methods are limited. In order to find new methods for diagnosis and treatment of COAD, people pay more and more attention to the discovery and functional research of new oncogenes and tumor suppressor genes of COAD. β 2-microglobulin (B2M) plays different physiological and pathological roles in tumor cells and nontumor cells. At present, there is no public report on the expression of B2M in COAD. In this study, the expression of B2M mRNA in COAD tissues was compared with that in normal tissues. The relationship between the expression of B2M mRNA and the stage, histological subtype, lymph node metastasis, TP53 mutation, and survival time of COAD was discussed. It was found that B2M is a potential tumor suppressor gene in COAD. The decreased expression of B2M after mutation can cause immune escape of COAD cells, thus affecting the therapeutic effect and prognosis. This study provides a new idea for the prevention and treatment of COAD.